The Relationship Between Liquid Limit and the Fully Softened and Residual Friction Angles in High-Plasticity Stiff Overconsolidated Clays: Hubungan Antara Liquid Limit dan Sudut Geser Fully Softened dan Residual pada High Plasticity Stiff Overconsolidated Clay - Muhammad Nafi' Mulyono; Kresno Wikan Sadono; Sri Prabadiyani Retno Wardani (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2026)
Landslide in high plasticity stiff overconsolidated clays frequently occur despite high safety factors obtained from analyses based on undrained shear strength. This is because the parameters used in such analyses do not adequately represent slope conditions subjected to repeated deformation and weathering. This study aims to identify the fully softened and residual shear strength parameters, to examine their relationship with the liquid limit (LL) for this soil type, and to find out the suitability of the relationship graph with that developed by Stark & ​​Hussain. Fully softened and residual shear strengths were obtained from direct shear slow reversal test. Remoulded specimens prepared using the slurry method and consolidated under normally consolidated conditions were used. Soil samples were collected from three landslide sites in Semarang. The test results indicate very high LL values (94-105%) with clay fractions exceeding 50% at all sampling locations. Overall, the results show consistency with the  regression bounds relating LL to fully softened and residual friction angles developed by Stark & Hussain. The correlation demonstrates good agreement and is applicable to local clayshales.